THE INFLUENCE OF INTELLECTUAL CAPITAL, GOOD CORPORATE GOVERNANCE, AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY PERFORMANCE - Romadon, Safiga Aulia; Damayanty, Prisila (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
The purpose of the study is to determine the influence of intellectual capital, good corporate governance (institutional ownership, managerial ownership, independent commissioner), and CSR on company performance. Researchers used population, namely manufacturing companies in the basic industrial & chemical sectors listed on the Indonesia Stock Exchange for the 2017-2020 period. The sampling technique is by purposive sampling method, which produces a total sample of 44 companies. The data analysis method in this study used multiple linear regression analysis. The results showed that intellectual capital did not have a significant positive effect on company performance. Meanwhile, institutional ownership, managerial ownership, and independent commissioners have a significant positive effect on company performance and corporate social responsibility does not have a significant negative effect on company performance. Keyword : Intellectul Capital, Institutional Ownership, Managerial Ownership, Independent Commissioner, Corporate Social Responsibility, and Corporate Performance